17 to 22 GHz quadrature RCL generator with load compensation - Esteban Eraso, Uxua; Sanchez-Azqueta, Carlos; Aznar, Francisco; Aldea, Concepción; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2024)
This paper presents solutions to improve the phase and magnitude errors of a quadrature generator due to the effect of load impedance. Quadrature and magnitude errors of less than 2° and 0.17 respectively, and insertion loss of less than 7 % at 19.5 GHz are achieved.